Cobalt and nickel impair DNA metabolism by the oxidative stress independent pathway1. Issue 11 (23rd October 2017) - Kumar, Vineet; Mishra, Rajesh Kumar; Kaur, Gursharan; Dutta, Dipak
Abstract : Cobalt and nickel exposure leads to DNA double-strand breaks, decelerating replication fork progression. In parallel, the metal ions inhibit RecBCD function to block SOS-mediated repair of the damaged DNA. Abstract : The oxidative stress that evolves under cobalt and nickel exposure is thought to exert toxicity, though the exact routes of such metal poisoning remain ambiguous. We revisited the metal toxicity in Escherichia coli to show that cobalt and nickel exposure at levels as low as 0.5 and 1 mM, respectively, visibly inhibits growth. We also observed that acidic conditions aggravated, while alkaline conditions alleviated the metal toxicity. Besides, 1 mM manganese, which is non-cytotoxic, as judged by the growth of E. coli, synergistically elevated cobalt and nickel stress. However, the metal toxicity did not lead to oxidative stress in E. coli . On the other hand, we show that cobalt and nickel, but not manganese, reduced the rate of DNA replication to 50% within 2 hours. Interestingly, the metal ions promoted DNA double-strand breaks but did not induce SOS repair pathways, indicating that the metal ions could block SOS induction. To test this, we show that cobalt and nickel, but not manganese, suppressed the nalidixic acid-induced SOS response. Finally, using an in vitro assay system, we demonstrated that cobalt and nickel inhibit RecBCD function, which is essential for SOS induction. Therefore, our data indicate that cobalt and nickel affect DNA replication, damage DNA, and inhibit the SOS repair pathway to exert toxicity.